D-Dimer-Driven Anticoagulation Reduces Mortality in Intubated COVID-19 Patients: A Cohort Study With a Propensity-Matched Analysis - Tassiopoulos, Apostolos K.; Mofakham, Sima; Rubano, Jerry A.; Labropoulos, Nicos; Bannazadeh, Mohsen; Drakos, Panagiotis; Volteas, Panagiotis; Cleri, Nathaniel A.; Alkadaa, Leor N.; Asencio, Anthony A.; Oganov, Anthony; Hou, Wei; et al. (Frontiers in Medicine, 2021)
Objective: Examine the possible beneficial effects of early, D-dimer driven anticoagulation in preventing thrombotic complications and improving the overall outcomes of COVID-19 intubated patients. Methods: To address COVID-19 hypercoagulability, we developed a clinical protocol to escalate anticoagulation based on serum D-dimer levels. We retrospectively reviewed all our first 240 intubated patients with COVID-19. Of the 240, 195 were stratified into patients treated based on this protocol (ON-protocol, n = 91) and the control group, patients who received standard thromboprophylaxis (OFF-protocol, n = 104). All patients were admitted to the Stony Brook University Hospital intensive care units (ICUs) between February 7th, 2020 and May 17, 2020 and were otherwise treated in the same manner for all aspects of COVID-19 disease. Results: We found that the overall mortality was significantly lower ON-protocol compared to OFF-protocol (27.47% versus 58.66%, P<0.001). Average maximum D-dimer levels were significantly lower in the ON-protocol group (7,553 ng/mL versus 12,343 ng/mL), as was serum creatinine (2.2 mg/dL versus 2.8 mg/dL). Patients with poorly controlled D-dimer levels had higher rates of kidney dysfunction and mortality. Transfusion requirements and serious bleeding events were similar between groups. To address any possible between-group differences, we performed a propensity-matched analysis of 124 of the subjects (62 matched pairs, ON-protocol and OFF-protocol), which showed similar findings (31% versus 57% overall mortality in the ON-protocol and OFF-protocol group respectively). Conclusions: D-dimer-driven anticoagulation appears to be safe in patients with COVID-19 infection and is associated with improved survival.